The poison garden - Marwood, Alex (Penguin Books, 2020)
"When nearly one hundred members of The Ark, a sinister apocalypse cult are found dead by poison at their isolated community in North Wales, those left alive are scattered to the winds with few coping skills and fewer answers. For twenty-three-year-old Romy, who has never known life outside the compound, learning how to live in a world she has been taught to fear is terrifying. Now Romy must start a new life for herself--and the child growing inside her. She is determined to find the rest of her family and keep her baby safe, no matter the cost. But as the horrors of her past start to resurface, she realizes that leaving her old life behind won't be easy. Outside the walls of The Ark, the real evil has only just begun. A brilliantly plotted, page-turning novel from "one of psychological suspense's best writers" (The Boston Globe), The Poison Garden will leave you stunned"--